Correlation of physical activity with cognition and mental health in medical students - Riskawati, Yhusi Karina; Rastramadhani, Faresa Aulia; Mulyani, Henny; Rindradi, Ridha Saniyyah; Mahendra, Muhammad Isa; Indradmojo, Christyaji; Nur, Aswaty (International Journal of Public Health Science (IJPHS), 2024)
Low physical activity increases the number of non-communicable diseases. This phenomenon occurs in medical students. This study aimed to determine the correlation between sedentary behavior and physical activity on cognition, mental health, cortisol, and brain derived neurotropic factor (BDNF). Using a cross-sectional design of observational study, eighty-six medical students were involved in this study. The subjects were interviewed to assess cognitive function and depression levels. Saliva was taken to measure cortisol and BDNF level. Bivariate analysis was performed using the Spearman test. Depression is the only variable that correlates significantly with habitual physical activity (p=0.025, r=-0.214). Sedentary behavior has a weak correlation with cognitive failure, anxiety, and depression ([p=0.046, r=0.216]; [p=0.039, r=0.223]; [p=0.011, r=0.273]). The results found that high physical activity improves mental health and cognition. This study suggested that physical activity can alleviate symptoms of depression and anxiety among medical students.